Paul Ricoeur diszdoktori avatás - Part 1
Audio recording of the event held on Sunday, March 9, 2003 when the Senate of CEU awarded its first honorary doctorate. The receiver of the honorary doctorate was Paul Ricoeur, Professor Emeritus of the University of Paris X–Nanterre, and of the University of Chicago. The ceremony took place in the CEU Auditorium and the laudation was given by CEU President and Rector Yehuda Elkana. After Paul Ricoeur’s response violinist Emese Kapcsos offers a short musical performance. Further presentations in the event are given by Jörn Rüsen (President, Kulturwissenschaftliches Institut, Essen), Aziz Al-Azmeh (CEU Distinguished Visiting Professor), Chris Lorenz (Professor of Philosophy of History, Vrije Universiteit, Amsterdam) and Sorin Antohi (CEU University Professor).